The Financial Impact of Hypofractionated Radiation for Localized Prostate Cancer in the United States. (2nd January 2019) - Moore, Assaf; Stav, Ido; Den, Robert B.; Gordon, Noa; Sarfaty, Michal; Neiman, Victoria; Rosenbaum, Eli; Goldstein, Daniel A.
Abstract : Background . Until recently, dose intensified radiotherapy was the standard radiation method for localized prostate cancer. Multiple studies have demonstrated similar efficacy and tolerability with moderate hypofractionation. In recent years there has been an increasing focus placed on understanding the cost and value of cancer care. In this study we aimed to assess the economic impact of moderate hypofractionation for payers in the United States. Methods . We performed a population-based analysis of the total cost of external beam radiotherapy (EBRT) for localized prostate cancer in the US annually. The national annual target population of patients treated with definitive EBRT was calculated using the Surveillance, Epidemiology, and End Results (SEER) database. Treatment costs for various fractionation schemes were based on billing codes and 2018 pricing by the Centers for Medicare and Medicaid Services (CMS). Results . We estimate that 27, 146 patients with localized prostate cancer are treated with EBRT annually in the US. The cost of standard fractionation in 45 or 39 fractions is US 26, 782 and 23, 625 per patient, respectively. With moderate hypofractionation in 28 or 20 fractions, the cost is US 17, 793 and 13, 402 per patient, respectively. The use of moderate hypofractionation would lead to 25-50% annual savings US 158, 315, 472-US 363, 213, 480 in the US. Conclusions . Moderate hypofractionation may have the potential to save approximately US 0.16-0.36 billion annually, likely without impacting survival or tolerability. This may lead to lower personal financial toxicity. It would be reasonable for public and private payers to consider which type of radiation is most suited to reimbursement.